New insights into the modification mechanism of Li-rich Li1.2Mn0.6Ni0.2O2 coated by Li2ZrO3. Issue 19 (28th April 2016) - Zhang, Jicheng; Zhang, Heng; Gao, Rui; Li, Zhengyao; Hu, Zhongbo; Liu, Xiangfeng
Abstract : The synergetic modification mechanism in Li2 ZrO3 -coated Li-rich Li1.2 Mn0.6 Ni0.2 O2 via a synchronous lithiation strategy has been proposed. Abstract : Lithium-rich Mn-based layered cathode materials have attracted wide attention due to their high specific capacity for lithium-ion batteries. However, some critical issues i.e. poor rate capability and voltage fade have limited their practical applications. Herein, we propose a synchronous lithiation strategy to coat Li-rich Li1.2 Mn0.6 Ni0.2 O2 (LMNO) with a thin layer of Li + -conductive Li2 ZrO3 . The obtained syn-Li2 ZrO3 @LMNO integrates the advantages of the Li2 ZrO3 coating and Zr 4+ doping, and shows a much higher rate capability and cycling stability than those of the counterpart post-Li2 ZrO3 @LMNO fabricated by a post-coating method. More importantly, the average voltage of syn-Li2 ZrO3 @LMNO has been enhanced by 0.15 V and the voltage decay has also been mitigated. New insights into the synergetic modification mechanism of the Li2 ZrO3 coating and Zr 4+ doping have been proposed. The coating layer of Li + -conductive Li2 ZrO3 alleviates the surface side reactions, suppresses the transition metal dissolution and enhances the Li-ion conductivity. Meanwhile, the doping and incorporation of Zr 4+ into the host structure accompanied by the Li2 ZrO3 coating expands the interplanar spacing and decreases Li/Ni mixing which facilitates Li + diffusion. In addition, the integration of the Li2 ZrO3 coating and Zr 4+ doping also further enhances the layered structure stability and mitigates the voltage fade during lithiation/delithiation cycles. Moreover, the proposed synchronous lithiation coating route avoids the duplicated high-temperature calcinations and can also be widely used to modify some other cathode materials.